PERENCANAAN PEMBANGKIT LISTRIK TENAGA MINI HIDRO (PLTM) PALUMBUNGAN, PURBALINGGA - Andi Prasetiyanto; Nizar Mahrus; Sri Sangkawati; Robert J. Kodoatie (Jurnal Karya Teknik Sipil, 2013)
Conditions Purbalingga areas potential for the development of Mini Hydro Power Plant, is the fundamental reason for empowering Klawing River District Bobotsari Purbalingga became a source of Mini Hydro Power Plant. The objective of mini hydro power plant planning is to  calculation of dependable flow, the calculation of the electricity which can be produced and made design of hydropower building. The method that apply for flood discharge plan calculation is Rational Method, Dependable flow analyzed by using Weibull Method. Dependable flow for mini hydro power plants amounted to 1.8 m3/s  and the power produced is 641 kW.